Gut epithelial and vascular barrier abnormalities in patients with chronic intestinal pseudo‐obstruction. Issue 8 (29th May 2019) - Boschetti, Elisa; Accarino, Anna; Malagelada, Carolina; Malagelada, Juan R.; Cogliandro, Rosanna F.; Gori, Alessandra; Tugnoli, Vitaliano; Giancola, Fiorella; Bianco, Francesca; Bonora, Elena; Clavenzani, Paolo; Volta, Umberto; et al.
Abstract: Background: Chronic intestinal pseudo‐obstruction (CIPO) is a rare condition due to severe impairment of gut motility responsible for recurrent subocclusive episodes. Although neuromuscular‐glial‐ICC abnormalities represent the main pathogenetic mechanism, the pathophysiology of CIPO remains poorly understood. Intestinal epithelial and vascular endothelial barrier (IEVB) abnormalities can contribute to neuroepithelial changes by allowing passage of harmful substances. Methods: To test retrospectively whether IEVB defects occur in patients with CIPO, we measured the jejunal protein expression of the major tight junction (TJ) components. CIPO patients were subdivided according to gut neuromuscular histopathology: apparently normal (AN); with inflammation (INF); or with degenerative alterations (DEG). The presence of occludin/claudin oligomers (index of TJ assembly), the amount of occludin, claudin‐4, and zonula occludens ‐1 (ZO‐1), and the expression of vasoactive intestinal polypeptide (VIP) and glial fibrillary acidic protein (GFAP) immunoreactivities were evaluated on jejunal full‐thickness biopsies using Western blot. Key Results: Oligomers were absent in the 73% of CIPO. Total occludin decreased in CIPO with AN and INF changes. Claudin‐4 was upregulated in CIPO with INF and DEG features. ZO‐1 and VIP expression decreased selectively in DEG group. GFAP increased in CIPO regardless the histopathological phenotype. Conclusions & Inferences: The absence of oligomers demonstrated in our study suggests that IEBV is altered in CIPO. The mechanism leading to oligomerization is occludin‐dependent in AN and INF, whereas is ZO‐1‐dependent in DEG. Our study provides support to IEVB abnormalities contributing to CIPO clinical and histopathological features. Abstract : The study aims to test retrospectively whether the intestinal epithelial and vascular barriers (IEVB) defects may occur in patients with chronic intestinal pseudo‐obstruction (CIPO), thus playing a role in CIPO physiopathology. We demonstrated abnormalities to protein expression and aggregation of major tight junction (TJ) components in the jejunum of CIPO patients suggesting that IEVB integrity is compromised in this condition. We propose that IEVB changes may contribute to neuro‐ICC‐muscular abnormalities in symptoms/manifestations detectable in CIPO patients. The identified molecular targets may be exploitable to design treatment options for patients with severe gut dysmotility.